A review: preparation of functionalised materials/smart fabrics that exhibit thermochromic behaviour - Civan, L.; Kurama, S. (Materials science and technology, 2021)
Colour transformation in thermochromic materials comes true with the phase transition in the material due to temperature amendments. By using thermochromic fibres, capsules, colourants, or pigments that respond to heat stimulus in various materials, these materials can be given functional properties. Studies on this subject in the literature are generally related to gaining thermochromic properties to main materials such as glass, concrete, asphalt, and wood. Other studies are related to the production of fibres with thermochromic properties and their use in thermochromic fabrics. In this study, the methods used in the progress of intelligent materials were examined. Developments in innovative, smart thermochromic fabrics were assessed. Despite technological progress, much research still needs to be done on textile practices of thermochromic materials.